Low-Frequency Repetitive Transcranial Magnetic Stimulation over Right Dorsolateral Prefrontal Cortex in Parkinson's Disease. (14th September 2020) - Zhuang, Sheng; Wang, Fu-Yu; Gu, Xin; Wu, Jia-Jing; Mao, Cheng-Jie; Gui, Hao; Chen, Jing; Liu, Chun-Feng
Abstract : Background . Repetitive transcranial magnetic stimulation (rTMS) is a promising therapeutic tool for Parkinson's disease (PD), and many stimulation targets have been implicated. We aim to explore whether low-frequency rTMS over the right dorsolateral prefrontal cortex (DLPFC) improves motor and nonmotor symptoms of individuals with PD. Methods . We conducted a randomized, single-blind, sham-controlled parallel trial to compare the effect of 10 consecutive daily sessions of 1 Hz rTMS over right DLPFC on individuals with idiopathic PD between active and sham rTMS group. Primary outcomes were changes in Unified Parkinson's Disease Rating Scale (UPDRS) part III and Nonmotor Symptom Questionnaire (NMSQ). Secondary outcomes were changes in UPDRS total score, Hamilton Rating Scale for Depression (HRSD), Pittsburgh Sleep Quality Index (PSQI), and Montreal Cognitive Assessment (MoCA). Assessments were completed at baseline, after treatment, and at 1 month, 3 months, and 6 months after treatment. Results . A total of 33 participants with PD were randomized. All participants completed the study and no severe adverse effect was noticed. Compared to baseline, active rTMS showed significant improvements in UPDRS part III and NMSQ at 1 month. Change of scores on UPDRS part III, HRSD, and PSQI persisted for 3 months after rTMS intervention. The beneficial effect on cognitive performance assessed by MoCA was maintained for at least 6 months in the follow-up. No significant changes were observed in the group with sham rTMS. Conclusions . Low-frequency rTMS of right DLPFC could be a potential selection in managing motor and nonmotor symptoms in PD.